Implementasi Soal berbasis Higher Order Thinking Skill (HOTS) dalam Pembelajaran Pengolahan Data Kelas V SDIT Ghilmani Surabaya - Yunitasari, Dinda Ayu; Najwa, Wulida Arina; Mansur, Nabilah (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the implementation of Higher Order Thinking Skills (HOTS)-based questions in teaching mathematics on data processing material in fifth-grade elementary school students. The research was conducted through comprehensive observation of lesson planning, delivery, and evaluation by the teacher. The results show that the questions used cover cognitive levels L4 to L6 based on the revised Bloom’s taxonomy. The questions were designed following the PISA assessment model, including complex multiple-choice and extended response formats to promote higher-order thinking. Evaluation was conducted holistically, encompassing cognitive, skills, and students’ spiritual and social attitudes. The teacher also assessed the learning process by observing students working individually and in groups. When students faced difficulties in understanding the questions, the teacher provided scaffolding to support independent thinking. The alignment between learning objectives, processes, and assessment was a key factor in the successful and meaningful implementation of HOTS questions, enhancing the quality of mathematics learning in elementary schools.